2011
DOI: 10.1038/labinvest.2010.170
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding-dependent glucocorticoid receptor activity promotes adipogenesis via Krüppel-like factor 15 gene expression

Abstract: Glucocorticoids, such as dexamethasone (Dex), have been used as in vitro inducers of adipogenesis. However, the roles of the glucocorticoid receptor (GR) in adipogenesis have not been well characterized yet. Here we show that inhibition of GR activity using the GR antagonist RU486 prevents human mesenchymal stem cell (hMSC) and mouse embryonic fibroblast (MEF) differentiation into adipocytes. Moreover, in MEFs isolated from GR knockout (GRnull) and GRdim mice deficient in GR DNA-binding activity, adipogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 44 publications
5
81
1
1
Order By: Relevance
“…Reporters containing these regions were induced in both A549 and Beas-2B cells by dex in transfection assays (Fig. 3E); the GBR in the first intron had previously been shown to respond to GR in other cell types (34). Together these data indicate that KLF15 is directly induced by GR signaling in A549 and Beas-2B cells through two glucocorticoid response elements (GREs).…”
Section: Gr-klf15-dependent Transcriptional Programmingmentioning
confidence: 63%
“…Reporters containing these regions were induced in both A549 and Beas-2B cells by dex in transfection assays (Fig. 3E); the GBR in the first intron had previously been shown to respond to GR in other cell types (34). Together these data indicate that KLF15 is directly induced by GR signaling in A549 and Beas-2B cells through two glucocorticoid response elements (GREs).…”
Section: Gr-klf15-dependent Transcriptional Programmingmentioning
confidence: 63%
“…Klf15 is a direct target of the GR (32,(53)(54)(55). We found divergent epigenetic chromatin marks on the Klf15 GRE that paralleled the change in gene expression elicited by differential GC steroid dosing.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, it has been reported that variants in KLF7 are protective against type 2 diabetes mellitus in Japanese and Danish patient cohorts (Kanazawa et al, 2005;Zobel et al, 2009). In addition, multiple laboratories have reported that KLF15 induces mouse adipocyte differentiation by increasing the expression of PPARγ (Mori et al, 2005), which has direct implications when correlated with the glucocorticoid-induced effects on mouse adipogenesis (Asada et al, 2011). Interestingly, all of these findings are based on tissue-specific constitutive knockout murine models, highlighting specific and important roles for KLFs in development and disease.…”
Section: Box 1 Klfs and Cancermentioning
confidence: 99%